Kesadaran Profetik : Upaya Mereduksi Neokolonialisme dalam Pendidikan - Nova Nafisah Zulfa; Muhamad Parhan (Pusat Riset dan Inovasi Nasional, 2024)
Educational neocolonialism is a planned policy of developed countries to maintain their influence over developing countries which is a continuation of past practices. In line with Paulo Freire's ideas in his book